Malignant Colo-Duodenal Fistula: A Case Report and Literature Review - Bhuiyan, Md Nur Hossain; Banik, Srikanta; Tuhin, Omor Faruk; Muhsin, Syed Md; Haque, Saiful; Ali, SM Ashraf; Yusuf, Omor Faruque (Journal of Chittagong Medical College Teachers’ Association, 2010)
Keywords: colo-duodenal fistula; malignant; clinical suspicion DOI: 10.3329/jcmcta.v20i2.5629 Journal of Chittagong Medical College Teachers' Association 2009: 20(2):53-55